Efforts To Increase Production Through Training On Liquid Organic Fertilizer (Lof) Preparation For Caulerpa Seaweed Farmers Group In Takalar Regency - Darmawati, Darmawati; Asni Anwar; Murni; Abdul Malik; Hamsah; Beddu Tang (OJS Universitas Muhammadiyah Gresik, 2025)
Liquid Organic Fertilizer (LOF) is a fertilizer produced from natural ingredients. LOF is highly beneficial for enhancing seaweed cultivation productivity due to its complex nutritional content. It is favored by the community as it is relatively inexpensive and environmentally friendly. However, seaweed farmers currently lack the knowledge and skills to produce liquid organic fertilizer. This activity aimed to equip seaweed farmers with the knowledge and skills needed to produce environmentally friendly liquid organic fertilizer (LOF) using locally available materials, thereby improving the production and quality of cultivated seaweed. The methods employed to address this issue included educational sessions on environmentally sustainable farming practices and practical training on producing LOF from banana stalks. Results from these activities indicated that Caulerpa farmers were generally unaware of the potential use of banana stalks as raw material for LOF production. Through these educational sessions, members of the